Peran Perpajakan dalam Perekonomian Indonesia: Tinjauan Sistem Perpajakan di Indonesia dan Dampaknya Terhadap Pertumbuhan Ekonomi - Didi Handono Syahputra; Muhammad Rizky Putra; Agung Anantha (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Taxation is one of the most important fiscal policy instruments, serving as the main source of state revenue and a tool for regulating the distribution of wealth. Taxation acts as the foundation of the economy in Indonesia and significantly influences its growth trajectory. Taxes are an obligation in social life where every level of society must contribute to paying contributions to the state in accordance with the applicable Constitution of the Republic of Indonesia. By analyzing applicable tax policies, this research evaluates the effectiveness of the Indonesian tax system in achieving economic development goals, including the structure and types of taxes in Indonesia, and challenges in implementing the tax system. Apart from that, this study also identifies the impact of taxation on economic growth.